P97 Protocol for a Systematic Review of Robotic Anti-reflux surgery to Examine Reporting of an Innovative Procedure: The RoboSurg Study. (8th April 2021) - Huttman, M; Robertson, H; Wood, F; Kiandee, M; Sewart, E; Gourbalt, L; Blencowe, N; ,; Huttman, Marc
Abstract: Background: Innovation in surgery is growing. The rigour of reporting of innovation must therefore be examined to ensure evaluations are thorough and transparent. The Idea, Development, Exploration, Assessmemt, Long-term follow-up (IDEAL) framework was developed in 2009 to help researchers evaluate innovative procedures. However, it is not known whether the IDEAL principles have been adopted into the reporting of robotic surgery. The aim of this study is to identify and summarise published literature for robotically assisted anti-reflux surgery, to understand whether evaluations are being performed in a robust way. Methods: Systematic literature searches were undertaken to identify studies relating to robotic anti-reflux surgery. All primary research studies pertaining to robotically-assisted surgery for adults with symptomatic gastro-oesophageal reflux disease were included. Studies examining multiple interventions, where the outcomes could not be separated, were excluded. Data will be doubly extracted using tailored online forms. Data extraction themes include: study characteristics, technique description and evolution, governance/ethical factors and outcome reporting. Data will be synthesised into tables and summarised in a narrative synthesis. A meta-analysis will not be performed as we aim to examine reporting, rather than the efficacy of robotically-assisted anti-reflux surgery. Results: 824 abstracts were identified, of which 80 were included for full text review. Summarised data will be used to propose a standard of reporting which will inform future work in the field. Conclusion: The findings will feed in to the other six arms of RoboSurg to examine reporting in robotic upper gastrointestinal surgery more generally.